Managerial performance, Tobin's Q, and the gains from successful tender offers - Lang, Larry H.P.; Stulz, RenéM.; Walkling, Ralph A. (Journal of Financial Economics, 1989)
For a sample of successful tender offers, we find that the shareholders of high q bidders gain significantly more than the shareholders of low q bidders. In general, the shareholders of low q targets benefit more from takeovers than the shareholders of high q targets. Typical bidders have persistently low q ratios prior to the acquisition announcement while target q ratios decline significantly over the five years before the tender offer. Our results are consistent with the view that takeovers of poorly managed targets by well-managed bidders have higher bidder, target, and total gains.